The Animal Style - Dianova, Julia (project baikal, 2020)
The article considers the animal style as a historico-cultural and art phenomenon and analyzes the representation of its stylized images in the urban environment of Perm, taking into consideration how semantics of such images reflects the historical and cultural heritage of the Perm land. The author highlights the possibilities to implement the artistic potential of the animal style in festive celebrations and leisure activities of the city. As a methodological basis, the conceptual ideas about the creative city of the British researcher Charles Landry, as well as the postulates of the theory of geocultural branding of the city presented in the works of the Russian scientist D. N. Zamyatin are used.